2011
DOI: 10.1177/1062860611413567
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Electronic Reporting of Laboratory Errors

Abstract: Laboratory testing is essential for diagnosis, evaluation, and management. The objective was to describe the type of laboratory events reported in hospitals using a voluntary electronic error reporting system (e-ERS) via a cross-sectional analysis of reported laboratory events from 30 health organizations throughout the United States (January 1, 2000, to December 31, 2005). A total of 37,532 laboratory-related events were reported, accounting for 14.1% of all reported quality events. Preanalytic laboratory eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 12 publications
(11 reference statements)
2
7
0
1
Order By: Relevance
“…In doing so, we refuted a potential case of infection transmission and identified an important step relevant to future studies of infection transmission in CF patients. Specimen mislabeling is among the most common preanalytic errors identified in clinical laboratories and is a particular risk in environments, such as CF clinics, where the same sample type is collected from multiple patients (50). Our data support the argument that transmission of Achromobacter among CF patients appears to be an uncommon event.…”
Section: Discussionsupporting
confidence: 78%
“…In doing so, we refuted a potential case of infection transmission and identified an important step relevant to future studies of infection transmission in CF patients. Specimen mislabeling is among the most common preanalytic errors identified in clinical laboratories and is a particular risk in environments, such as CF clinics, where the same sample type is collected from multiple patients (50). Our data support the argument that transmission of Achromobacter among CF patients appears to be an uncommon event.…”
Section: Discussionsupporting
confidence: 78%
“…In a study by Syndman et al, after extensive analysis of laboratory reports in 30 healthcare organizations, they found that laboratory events before analysis were the most common (81%) errors. The top three examples of errors were unlabeled specimens (18.7%), wrongly labeled specimens (16.3%), and improper collection (13.2%) [ 20 ]. In the study of Makary et al, in the evaluation of 21,351 surgical specimens, 11 cases (0.05%) of inappropriate label errors were discovered, which led to assigning the specimen to the wrong patient [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory information systems (LISs) are HISs that can be used to order tests, process samples, receive results, and create and communicate reports (8). LISs can improve laboratory processes and documentation accuracy of laboratory test results.…”
Section: Introductionmentioning
confidence: 99%
“…LISs can improve laboratory processes and documentation accuracy of laboratory test results. Nevertheless, research has shown that the use of LISs can have major errors (8)(9)(10). Laboratory errors can lead to wrong diagnosis, inappropriate care, delayed treatment, poor clinical research, increased costs, and endanger patients' lives (9).…”
Section: Introductionmentioning
confidence: 99%